What Does GPA in an Urban High School Actually Mean? - Robbie J. Steward; Martin F. Hill; Douglas M. Neil; Tiffany Pritchett; Ah-Sha-Ni Wabaunsee (Educational Considerations, 2008)
The purpose of this researcher-school collaborative study was to examine factors which might be intervenable by urban high school counselors in assisting at-risk students. There were two primary objectives. The first was to examine the degree to which urban adolescents’ academic competence predicts cumulative GPA.
Keywords: students; success; urban; high school; teacher; perceptions; academic; performance; grade point average (GPA); regression analysis